T-violating effect in $ν_τ (\bar{ν}_τ)-$nucleon quasielastic scattering - A. Fatima, M. Sajjad Athar and, S. K. Singh (SciPost Physics Proceedings)
The production cross sections and polarization observables of the $τ$ leptons produced in the $|Δ S| = 0$ and $1$ induced $ν_{τ}(\bar{ν}_{τ})-N$ quasielastic scattering have been studied. The effect of T violation, in the case of $Δ S=0$ and 1 processes, and the SU(3) symmetry breaking effects, in the case of $Δ S=1$ processes, on the total scattering cross sections as well polarization observables are explored. Experimentally, it would be possible to observe these effects in the forthcoming (anti)neutrino experiments like DUNE, SHiP and DsTau.